Potential antitumor activity of nonsteroidal anti-inflammatory drugs against Ehrlich ascites carcinoma in experimental animals - Ellethy, Abousree Taha (International Journal of Health Sciences, 2019)
Objectives: Although there is evidence that nonsteroidal anti-inflammatory drugs (NSAID) (e.g., celecoxib [Cxb]) can reduce the occurrence of cancer, the precise mechanism remains under study. The current study aimed to investigate the possible antitumor activity of a selective cyclooxygenase-2 inhibitor on solid tumors, its effect on antioxidant status, and ability to prevent angiogenesis. Materials and Methods: Solid carcinomas were induced in female Swiss albino mice. Fifty adult female mice were randomly selected and categorized into five groups. The effects of Cxb on hepatic oxidative parameters and the serum level of vascular endothelial growth factors (VEGF) were investigated in parallel to liver histopathological examinations. Biochemical measurements of hepatic malondialdehyde, superoxide dismutase (SOD) activity, hepatic catalase (CAT) activity, and reduced glutathione (GSH) were estimated in liver homogenates prepared from mice in each study group. Results: The induction of solid tumors in female albino mice was associated with a significant elevation in hepatic lipid peroxidation, whereas the activity of antioxidant enzyme NSAID and CAT was significantly decreased. The level of reduced GSH was decreased. Serum levels of VEGF were significantly increased in tumor-bearing mice compared with normal control mice. These changes were ameliorated when mice were treated with Cxb either before or after the induction of tumors. Antioxidant enzymes were significantly increased, and the serum level of VEGF was significantly reduced compared with the levels in tumor-bearing mice. Conclusion: Cxb exerts antitumor activity through antioxidative and antiangiogenic activities.